The Numerical Methods for Solving Euler System of Equations in Reproducing Kernel Space $H^2(R)$ (Journal of Computational Mathematics, 2001)
A new method is presented by means of the theory of reproducing kernel space and finite difference method, to calculate Euler system of equations in this paper. The results show that the method has many advantages, such as higher precision, better stability, less amount of calculation than any other methods and reproducing kernel function has good local properties and its derived function is wavelet function.
Keywords: Euler system of equations; Reproducing kernel method; Finite difference method; Wavelet function.